HAK CUTI TAHUNAN PADA PEKERJA DENGAN PKWT (PEKERJA KONTRAK) (Lex Journal: Kajian Hukum & Keadilan, 2018)
This thesis entitled " ANNUAL LEAVE RIGHT ON WORKERS WITH PKWT (CONTRACT WORKERS)", writing on research methods used juridical normative, using the approach of the law (Statute Approach) and the conceptual approach (Conceptual Approach). Formulation of the problem in this paper are: (1) What is a worker in article 79 of Law No. 13 of 2003 must have status as a permanent workers?, (2) What are the legal remedies that can be done for the contract worker / employee that do not get their annual leave entitlements? Resulting from the approach that the first formulation of the problem, the status of the workers mentioned in article 79 of Law No. 13 of 2003 on employment do not have status as permanent workers, provided that an employee has worked for 12 consecutive months, the employee is entitled to receive annual leave entitlements. While in the second formulation of the problem, discuss the legal remedies that can be done by a worker if he does not get his annual leave entitlements. Workers can resolve the dispute to the Industrial Relations Settlement.Keywords :Annual Leave Entitlement, Contract Workers, Industrial Relations Settlement.